PERANCANGAN PROTOTYPE JEMURAN OTOMATIS MENGGUNAKAN SENSOR AIR DAN SENSOR LDR BERBASIS MIKROKONTROLER ARDUINO UNO DENGAN METODE FLC - Harahap, Nur Apipah (STMIK Budi Darma, 2018)
Indonesia is a tropical country that has two seasons, rainy and summer. when the rainy season arrives, the majority of people feel anxious when drying their clothes. The anxiety will increase when drying clothes but is outside the house, and at home, there are no people. From this incident, people were reluctant to hang clothes in the open, because they were afraid that their clothes would get wet when they were left by their owners while doing activities outside the house. FLC (Fuzzy Logic Controller) method is a method that only knows 0 and 1 in operation. The vague operation, there is no gray only black or white. And this is something logical. From the description of the problems that occur, the authors find the idea to make clothesline pullers that can work automatically, even though there are already some people who have made the same mechanism using Arduino Mega 2560, with just a dark and bright condition, here the author wants to try to renew the way the mechanism of the device works by using Arduino Uno, and look for conditions when the heat is hot but rain, then this method answers what must be done by applying the logic of Fuzzy Logic Controller inside the Arduino Uno microcontroller.